The occidental perspective of the accession negotiations between Turkey and the European Union - EMILIA NICOLETA SCHIOP (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This article examines Turkey’s Europeanization efforts in the context of the current European crisis. The introductory paragraph sets the stage for the rest of the paper. The paper analyses Turkey’s negotiations with the European Union, focusing on the most significant economic and legal chapters as the Turkish government moves closer to applying for EU accession (according to the annual reports of the European Commission).Method: European Commission reports and other official documents are used to analyze the talks. The individual’s impact will be highlighted in relation to this method of investigation. In this instance, we consult the related institutions’ publicly available records. The EU’s most important resources are typically discussed and analyzed at this stage of negotiations, with opinions being highly contextualized.Findings: To function smoothly, the European Union needs its neighboring countries to be cooperative partners. Official relations with the Turkish state could be jeopardized, particularly due to the unstable situation in Turkey and internationally if official discussions on potential integration were suspended.Implications/Novel Contribution: For the European Court of Human Rights article 46 mandate to be fulfilled, Turkey must increase its cooperation with the Council of Europe and its relevant bodies and institutions to consider key recommendations and implement all human rights decisions. Integrity must be prioritized.